Association between Autoimmune Rheumatic Diseases and the Risk of Dementia. (30th April 2014) - Lu, Kang; Wang, Hao-Kuang; Yeh, Chih-Ching; Huang, Chih-Yuan; Sung, Pi-Shan; Wang, Liang-Chao; Muo, Chih-Hsin; Sung, Fung-Chang; Chen, Han-Jung; Li, Ying-Chun; Chang, Li-Ching; Tsai, Kuen-Jer
Abstract : Aim . Autoimmune rheumatic diseases (ARD) are characterized by systemic inflammation and may affect multiple organs and cause vascular events such as ischemic stroke and acute myocardial infarction. However, the association between ARD and increased risk of dementia is uncertain. This is a retrospective cohort study to investigate and compare the risk of dementia between patients clinically diagnosed with ARD and non-ARD patients during a 5-year follow-up period. Methods . Data were obtained from the Longitudinal Health Insurance Database 2000 (LHID2000). We included 1221 patients receiving ambulatory or hospitalization care and 6105 non-ARD patients; patients were matched by sex, age, and the year of index use of health care. Each patient was studied for 5 years to identify the subsequent manifestation of dementia. The data obtained were analyzed by Cox proportional hazard regression. Results . During the 5-year follow-up period, 30 ARD (2.48%) and 141 non-ARD patients (2.31%) developed dementia. During the 5-year follow-up period, there were no significant differences in the risks of any type of dementia (adjusted hazard ratio (HR), 1.18; 95% CI, 0.79–1.76) in the ARD group after adjusting for demographics and comorbidities. Conclusions . Within the 5-year period, patients with and without ARD were found to have similar risks of developing dementia.